6‐Nitroazolo[1, 5‐a]pyrimidin‐7(4H)‐ones as Antidiabetic Agents. Issue 12 (20th November 2017) - Spasov, Alexander A.; Babkov, Denis A.; Sysoeva, Valentina A.; Litvinov, Roman A.; Shamshina, Darya D.; Ulomsky, Evgeny N.; Savateev, Konstantin V.; Fedotov, Viktor V.; Slepukhin, Pavel A.; Chupakhin, Oleg N.; Charushin, Valery N.; Rusinov, Vladimir L.
Abstract : Prevention of the formation of advanced glycation end‐products (AGEs) is a reliable approach to achieve control over hyperglycemia and the associated pathogenesis of diabetic vascular complications. In these terms, new synthetic approaches to 6‐nitroazolo[1, 5‐ a ]pyrimidines have been developed on the basis of the promising antiglycation activity of their structural analogues, such as azolo[5, 1‐ c ][1, 2, 4]triazine‐4(1 H )‐ones. A number of nitroazolopyrimidines were obtained by using nitration, chlorodeoxygenation, and amination reactions, and their antidiabetic properties were elucidated in vitro . It was shown that triazolo[1, 5‐ a ]pyrimidine‐7(4 H )‐ones exhibit a higher antiglycation activity than the corresponding 7‐alkylamino analogs and aminoguanidine, as the reference compound. It is suggested that this kind of activity can be associated with the chelating properties possessed by the synthesized 6‐nitro‐7‐oxoderivatives. Furthermore, the compounds obtained were tested for their inhibitory activity against dipeptidyl peptidase 4 (DPP4), glycogen phosphorylase, and α‐glucosidase in vitro, but their activities proved to be significantly inferior to those of the reference compounds. Abstract : The compounds of the new 6‐nitroazolo[1, 5‐ a ]pyrimidine series show promising antiglycation activity. In particular, 2‐(α‐furyl)‐6‐nitro‐1, 2, 4‐triazolo[1, 5‐ a ]pyrimidin‐7‐one demonstrated inhibition of the formation of advanced glycation end‐products (IC50  = 50.35 μM) at one order of magnitude higher than that of the reference compound, aminoguanidine (IC50  = 765.00 μM).